Social media strategy in the sporting goods industry : potential application for Brooks Sports, Inc. - Mahoney, Tara Q.; Lovich, Justin; Brady, Lawrence (London : SAGE Publications: SAGE Business Cases Originals, 2019)
Social media is an ever-present part of society. Sporting goods companies have acknowledged the necessity of embedding social media into their overall brand strategy. Many companies such as Nike, Adidas, and Under Armour spend a considerable amount of time and money to engage their customers online. Niche brand Brooks has a more limited social media presence. In addition, they have a goal of doubling their revenue from $500 million to $1 billion by 2020. Social media strategy will play a major role in achieving this goal. Students are selected to work on a social media strategy team and are tasked with providing recommendations in the creation of a comprehensive social media strategy to meet organizational goals and objectives.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Brooks Sports, Inc; Social media; Strategic planning; Sporting goods industry; Branding (Marketing)